Damage Analysis of CFRP under Impact Fatigue - George Tsigkourakos; Vadim V. Silberschmidt; Ian A. Ashcroft (Shock and Vibration)
In recent years carbon fibre reinforced polymers (CFRPs) have become some of the most important structural materials in the aerospace industry due to their excellent stiffness and strength to weight ratios. The real-life loading histories of aerospace composite components and structures involve the generation of transient loads that can propagate as cyclic impacts. This phenomenon is known as impact fatigue (IF). Such loads can cause various types of damage in composites, including fibre breakage, transverse matrix cracking, de-bonding between fibres and matrix and delamination, resulting in a reduction of residual stiffness and a loss of functionality.